LONGITUDINAL DIFFERENT-WALL OF HOLLOW CASTINGS AT FORMING OF INTERNAL SURFACE OUT OF MELT WITHOUT APPLICATION OF ROD - E. I. Marukovich; V. F. Bevza; V. P. Grusha (Литьë и металлургия)
The reasons of occurrence of axial polythickness of hollow slugs at forming of internal surface of melt without application of stick are investigated. The ways of its minimization are determined.